2001
DOI: 10.1046/j.1523-1755.2001.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 inhibits ischemic and cisplatin-induced acute renal injury

Abstract: IL-10 protects against renal ischemic and cisplatin-induced injury. IL-10 may act, in part, by inhibiting the maladaptive activation of genes that cause leukocyte activation and adhesion, and induction of iNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
275
5
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(309 citation statements)
references
References 64 publications
26
275
5
3
Order By: Relevance
“…Among potential candidates, we focused on IGF-1, which possesses mitogenic and antiapoptotic properties 27,31 ; TGF-␤, which is involved in tubulogenesis and in the dedifferentiation of adult tubular cells 32,33 ; and IL-10, a cytokine with anti-inflammatory activities. 34 By using specific functional blocking antibodies, we evidenced a determinant role of IGF-1 in PTEC proliferation induced by MSC. MSC constitutively expressed IGF-1 mRNA and protein, as already described, 17,35 with protein levels remarkably higher than those detected in control or cisplatin-treated PTEC.…”
Section: Discussionmentioning
confidence: 82%
“…Among potential candidates, we focused on IGF-1, which possesses mitogenic and antiapoptotic properties 27,31 ; TGF-␤, which is involved in tubulogenesis and in the dedifferentiation of adult tubular cells 32,33 ; and IL-10, a cytokine with anti-inflammatory activities. 34 By using specific functional blocking antibodies, we evidenced a determinant role of IGF-1 in PTEC proliferation induced by MSC. MSC constitutively expressed IGF-1 mRNA and protein, as already described, 17,35 with protein levels remarkably higher than those detected in control or cisplatin-treated PTEC.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have reported the influence of IL-10 in attenuating inflammation and kidney injury in animal models of acute GN, 17,18 CKD, 35 cisplatin nephrotoxicity, 14,36,37 and ischemic injury. 14 Further, animal studies in a variety of other disease settings have also demonstrated similar protective properties of IL-10 and have even reported that the cytokine creates an environment conducive for regenerative adult wound healing. [38][39][40][41][42] This is the first perioperative clinical study, to our knowledge, that has found a significantly protective association of a cytokine on all-cause mortality after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Accordingly, IL-6 has been suggested to exacerbate renal injury, 12,13 while IL-10 has been shown to confer protective effects. [14][15][16][17][18][19] We hypothesized that our cohort would also show these trends. Notably, a preclinical study 20 has demonstrated that IL-10 protects against renal ischemia through the induction of neutrophil gelatinase-associated lipocalin (NGAL), an established AKI biomarker that our group has previously studied.…”
mentioning
confidence: 99%
“…Free heme is cytotoxic, and heme clearance reduces oxidative stress and apoptosis (58), which is assumed to promote resolution of inflammation. IL-10 attenuates the host response to microbial antigens, to cytokines and chemokines (21,59), to ischemia reperfusion, and to some drug-induced injuries (13,60). This limits tissue damage, but the persistence of IL-10 leads to immune suppression and to impaired pathogen clearance in infection (61).…”
Section: Was Detected (Panels A-c) Dcm/co (1-h Exposure) Caused Robumentioning
confidence: 99%